Tantangan dan Strategi Pengelolaan Pembiayaan Pendidikan di Madrasah Swasta - Rahayu, Syarifah Dwi; Lemmy, Paradita Kumala (Pase: Journal of Contemporary Islamic Education, 2024)
Financial management in private madrasahs plays a fundamental role in ensuring the sustainability and quality of Islamic education services. This study aims to analyze the implementation, challenges, and strategies of financial management in Indonesian private madrasahs within the context of effectiveness, accountability, and transparency. Using a qualitative approach with a descriptive method, this research employs library-based data collection by reviewing books, scholarly journals, policy reports, and government regulations related to educational financing. The findings reveal that madrasah financial management operates through three main stages: planning (budgeting), implementation (accounting), and supervision (auditing). These stages collectively form the backbone of an effective and efficient financial system. Sources of madrasah funding include government allocations, parental contributions, community support, alumni donations, and waqf institutions. However, private madrasahs face several challenges, such as dependency on limited funding sources, weak accounting systems, and inadequate managerial competence. To overcome these obstacles, madrasahs need to diversify their funding sources, strengthen managerial capacity, and adopt technology-based accounting systems that ensure transparency and accountability. This study concludes that financial management in private madrasahs is not merely a technical or administrative process but also reflects the integration of economic rationality with spiritual ethics, forming the foundation for sustainable and value-driven Islamic educational governance.